Implementasi Keteladanan Guru Pendidikan Pancasila dan Kewarganegaraan dalam Meningkatkan Karakter Siswa - Gustri Wanna Gea; Darisalim Telaumbanua; Hendrikus Otniel Nasozaro Harefa; Adrianus Bawamenewi (Pusat Riset dan Inovasi Nasional, 2025)
Exemplary is a good attitude and morals that exist in a person who can be used as a role model. The study aims to determine the implementation and impact of exemplary Pancasila and citizenship education teachers in improving the character of class VIII students at SMP Negeri 4 Idanogawo. The research method is qualitative research, descriptive approach. Data were collected using observation, interview, and documentation techniques. Data analysis techniques are carried out by collecting, reducing, analyzing data and drawing conclusions. The results of the study: first, the implementation of exemplary Pancasila and citizenship education teachers in improving student character is to be a role model through real actions such as honesty, discipline, responsibility and politeness in interacting, so as to have a positive influence on the development of students' attitudes and behavior in everyday life; second, the impact of exemplary implementation of Pancasila and citizenship education teachers for students is an increase in better student attitudes and behavior in the classroom and in the school environment.